Front-end chip for Silicon Photomultiplier detectors with pico-second Time-of-Flight resolution - Stankova, Vera; Briggl, Konrad; Chen, Huangshan; Gil, Alejandro; Harion, Tobias; Munwes, Yonathan; Shen, Wei; Schultz-Coulon, Hans-Christian (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2016)
A mixed-mode readout Application Specific Integrated Circuit (STIC3) has been developed for high precision timing measurements with Silicon Photomultipliers (SiPM) for medical imaging and particle physics applications. The STiC3 is a 64-channel chip, with fully differential analog front-end for cross-talk and electronic noise immunity. The time and charge information from the SiPM signals are encrypted into two time stamps generated by integrated Time to Digital Converter (TDC) modules with 50ps time binning. The TDC data is stored in an internal memory and transferred to a PC via a 160MBit/s serial link using an 8/10 bit encoding. The chip provides an input bias tuning in a range of 0-900mV to compensate the breakdown voltage variation of individual SiPMs. The TDC jitter together with the digital part is around 37ps. A Coincidence Time Resolution (CTR) of 213.6ps FWHM has been obtained with 3.1×3.1×15m2 LYSO:Ce scintillator crystals and Hamamatsu SiPM matrices (S12643-050CN(X)). Characterization measurements with the chip and its integration into the external plate of the EndoTOFPET-US prototype are presented.
Available online 23 November 2015
Gesehen am 13.05.2020